Robustness and accuracy of cell division in Escherichia coli in diverse cell shapes. - Männik, J; Wu, F; Hol, F; Bisicchia, P; Sherratt, D; Keymer, J; Dekker, C (2012)
Cell division in typical rod-shaped bacteria such as Escherichia coli shows a remarkable plasticity in being able to adapt to a variety of irregular cell shapes. Here, we investigate the roles of the Min system and the nucleoid-occlusion factor SlmA in supporting this adaptation. We study "squeezed" E. coli in narrow nanofabricated channels where these bacteria exhibit highly irregular shapes and large volumes. Despite the severely anomalous morphologies we find that most of these bacteria maintain their ability to divide into two equally sized daughters with an accuracy comparable to that of normal rod-shaped cells (about 4%). Deletion of either slmA or minC shows that the molecular systems associated with these genes are largely dispensable for accurate cell division in these irregular cell shapes. Using fluorescence time-lapse microscopy, we determine that the functionality of the Min system is affected by the cell shape, whereas the localization of a nucleoid relative to the cell division proteins (the divisome) remains unperturbed in a broad spectrum of morphologies, consistent with nucleoid occlusion. The observed positioning of the nucleoid relative to the divisome appears not to be affected by the nucleoid-occlusion factor SlmA. The current study underscores the importance of nucleoid occlusion in positioning the divisome and shows that it is robust against shape irregularities.